Hollow - Peckham, Caroline; Valenti, Susanne (Crown of hearts and chaos, 2025)
"The Great Hunt begins once every fifty years and only the Champions willing to face death to shatter the curse dare to enter. The Champions...and me. I'm no warrior, no swordsmith, and certainly no Fae, but the forest is my only hope. To enter those trees is to walk willingly to my demise. But I need the boon the forest will grant the winner and I'm willing to risk it all for a chance at claiming it. I just never expected to face him beneath those trees. The beast who strikes fear into the desperate people of all lands. The monster who commands the legion of Hollows and makes our plight a thousand times worse. Prince Bane intends to be the death of me. But I have an oath to fulfil before I'll let him have me. And I'll do whatever it takes to achieve it. I am Ferris Creed and I'm going to unite the lost spirits who once bound the wandering trees in place, return the scattered amulets to the core of its corruption, and use the winner's boon to change my fate. Come wretchedness or torment, through trickery and deception, I will get what I came here for. And no one will stand in my way. Not even Prince Bane." --